Sosialisasi Mitigasi Bencana di Daerah Wisata Pantai Desa Sindanglaya Anyer Banten - Rahmawati Rahmawati; Maulana Yusuf; Ardiyansah Ardiyansah (WINDRADI: Jurnal Pengabdian Masyarakat, 2025)
Disaster mitigation constitutes an essential phase in disaster management, aiming to reduce potential impacts through early identification of warning signs. At this stage, indicators of possible hazards are recognized, enabling communities to take anticipatory actions to safeguard themselves. This community engagement program focused on disaster mitigation socialization for residents in the coastal tourism area of Sindanglaya Village, which is highly vulnerable to natural hazards. The initiative aimed to equip local residents to serve as informants for tourists while also enhancing community awareness of disaster risks. The materials were delivered by geography experts, Tagana members, local community representatives, and the Regional Disaster Management Agency (BPBD). The results indicated that local wisdom, expressed through ancestral disaster-related folktales, serves as an enduring form of traditional mitigation. Additionally, communities utilize kentongan (wooden slit drums) and the mosque’s call to prayer as early warning signals during potential hazard events. Evacuation route signs have been installed at key locations, directing residents to move toward hilly areas at least five kilometers from the shoreline. These findings demonstrate that combining scientific knowledge, community participation, and local wisdom effectively strengthens disaster preparedness in coastal regions.